2017
DOI: 10.1016/j.jclepro.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Flood footprint of the 2007 floods in the UK: The case of the Yorkshire and The Humber region

Abstract: International headlines over the last few years have been dominated by extreme weather events, and floods have been amongst the most frequent and devastating. These disasters represent high costs and functional disruptions to societies and economies. The consequent breakdown of the economic equilibrium exacerbates the losses of the initial physical damages and generates indirect costs that largely amplify the burden of the total damage. Neglecting indirect damages results in misleading results regarding the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 22 publications
0
27
0
8
Order By: Relevance
“…As the most common of natural disasters, floods are selected as the main type of multiple natural disaster in this study and the concept of flood footprint that is proposed by Mendoza-Tinoco et al [25] is applied here to indicate the total economic impact caused by floods through direct and indirect methods. In particular, direct flood footprint (DFF) analysis shows the direct damage to physical capital, people and natural resources; while the indirect approach refers to the physical damage-induced influence on an economic system during the post-disaster recovery period.…”
mentioning
confidence: 99%
“…As the most common of natural disasters, floods are selected as the main type of multiple natural disaster in this study and the concept of flood footprint that is proposed by Mendoza-Tinoco et al [25] is applied here to indicate the total economic impact caused by floods through direct and indirect methods. In particular, direct flood footprint (DFF) analysis shows the direct damage to physical capital, people and natural resources; while the indirect approach refers to the physical damage-induced influence on an economic system during the post-disaster recovery period.…”
mentioning
confidence: 99%
“…In this paper, the standard parameters are defined based on the existing literature and data from the WorldBank (): The economic parameters are set in combination with the parameter set of Hurricane Katrina in the United States from Hallegatte () and the international trade time to import and export from the WorldBank (). The threshold of the parameter uncertainty range is set to upward and downward variations of 30% of the standard parameters; this range refers to the flood footprint model (Mendoza‐Tinoco et al, ), which is influenced by capital and labor.…”
Section: Research Methods and Datamentioning
confidence: 99%
“…In addition, to verify the robustness of the model, we defined different verification groups to determine whether the model simulation results are orderly and stably distributed within the scope of uncertainty (Mendoza‐Tinoco et al, ). In addition, the parameter values of each group are taken in accordance with the uncertainty range in the interval of 5%, that is, a total of 13 groups.…”
Section: Research Methods and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by other research. In the UK, at the end of May, 11-12 months after the floods, local authorities estimated that about 75% of households were back in their homes [25] and the economy of the Yorkshire and Humberside Region had returned to pre-disaster production levels within 14 months [55]. In Germany, a survey of 752 flood-prone residents 18 months after the event revealed that 52% of respondents had almost fully repaired the damage to their buildings and 28% of respondents said they were back to normal [33].…”
Section: (B) Speed Of Recoverymentioning
confidence: 99%